Ефективність та прибутковість: теоретичний аспект - Стригуль, Лариса Станіславівна; Тур, Ганна Євгенівна; Нгуєн, Тхі Мі Хань (My University, 2019)
У статті розглянуті питання теоретичного узагальнення та систематизації підходів щодо визначення економічної сутності категорій “ефективність” та “прибутковість” і виокремлення або, навпаки, поєднання спільних рис і характеристик щодо їхніх сутнісних ознак з урахуванням відмінностей та визначення рівня підпорядкованості категорій. Ефективність як економічна категорія відображає дію об’єктивних економічних законів, яка проявляється в результативності виробництва, тобто в прибутковості діяльності загалом. Прибутковість є основою економічної ефективності діяльності, що відображає кінцевий корисний ефект від застосування засобів виробництва і живої праці, а також сукупних їхніх внесків. Категорії "ефективність" та "прибутковість" є багатозначними та багатовимірними. Проведені дослідження визначень ефективності та прибутковості мають теоретико-практичну значущість щодо удосконалення визначення категорій та їхньої підпорядкованості, що дає змогу одержати комплексне уявлення за всіма аспектами на засадах розрахунку відповідних показників прибутковості, що і створює підґрунтя для об’єктивного оцінювання ефективності.

The article deals with issues of theoretical generalization and systematization of approaches to defining the economic essence of the concepts of efficiency and profitability and isolation, or, conversely, a combination of common features and characteristics on their essential features taking into account differences and to determine the level of subordination of categories. The economic efficiency of economic entities, regardless of their organizational and legal form and area of operation, depends on the level of provision of enterprises with the resources and financial potential, their rational ratio and effective use in the process of economic activity. Efficiency as an economic category reflects the action of objective economic laws, which is manifested in the efficiency of production is in the profitability of the activity as a whole. Profitability is the basis of economic efficiency of the activity, as a whole reflects the ultimate beneficial effect of the use of means of production and living labor, as well as their total investment. The profitability of an enterprise is the most important criterion for the activity of any enterprise, since in the absence of strategic directions of development and the proper level of profitability, the enterprise can gradually lose liquidity and eventually go bankrupt, and ensuring the profitability of the enterprise is an indicator of the stabilizing effect of its development. The categories “efficiency” and “profitability” are multifaceted and multidimensional, so many domestic and foreign scientists pay attention to this issue. Thus, the study of the features of determining and highlighting the essential elements of filling the categories of “efficiency” and “profitability”, taking into account the features of their application in the financial analysis of complex economic phenomena and processes, is a timely and relevant task. The conducted studies of the definitions of efficiency and profitability have theoretical and practical significance for improving the definition of categories and their subordination, allows to obtain a comprehensive view on all aspects, based on the calculation of the relevant indicators of profitability, and creates the ground for an objective evaluation of efficiency.
Efficiency and profitability: theoretical aspect
Keywords: ефективність; прибутковість; комплексний підхід; ресурсний підхід; efficiency; profitability; integrated approach; resource approach